Bodarc, Butler County - Voth, Evan (Kansas State University, The Chapman Center for Rural Studies, 2013)
This document provides a comprehensive history of the lost community of Bodarc (Bois D’ Arc) from the time that the Osage Indians settled the land to present day. Bodarc was unofficially founded in 1875 and included a mill, general store, schoolhouse, church, and cemetery. This study incudes newspaper clippings, personal records, photographs, interviews, and information obtained from the Butler County Historical Society.
Evan Voth, “Bodarc, Butler County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/121.
Keywords: Bloomington Township; Bodarc; Bois D'Arc; Bradford Mill; Butler County; Samuel Rankin